A highly sensitive magnetic field sensor based on FBG and magnetostrictive composite with oriented magnetic domains. (15th February 2022) - Peng, Jun; Zhang, Shuo; Jia, Shuhai; Kang, Xilong; Yu, Hongqiang; Yang, Shuming; Wang, Shun; Yang, Yaowen
Highlights: A highly sensitive optical fiber magnetic field sensor. Magnetostrictive composite with oriented magnetic domains used as sensor probe. An FBG encapsulation structure design for sensitivity enhancement. Sensor sensitivity is 3–4 times that of other sensors in the literature. Abstract: In this paper, an optical fiber sensor for magnetic field measurement is proposed using a fiber Bragg grating (FBG) and a magnetostrictive composite. The FBG coated by the composite is used as the magnetic field transducer. The composite consists of the Terfenol-D particles and a matrix of epoxy resin. An external magnetic field is employed to orient the magnetic domains in the composite. An FBG encapsulation structure is designed to enhance sensor sensitivity. The results of the calibration test demonstrate that the sensor has good repeatability and a high sensitivity of 9.83 pm/mT, which is about 3 ∼ 4 times higher than other sensors based on the similar principle in the literature. The dynamic test shows a fast response of the sensor to the dynamic magnetic field. This optical fiber sensor has the instinct advantage of immunity to electromagnetic interference and possesses good potential in power engineering applications.